Liability of legal entities in industrial property rights in the light of Iranian law (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Criminal liability is the ability to invoke criminal acts against the person or persons who committed them. In order for criminal responsibility to be realized and the crime to be attributable to the perpetrator, its elements must be present. Although the criminal responsibility of a legal entity was not denied in the Islamic Penal Code adopted in 1370, but it was accompanied by the silence of the legislator, although it is known and punishable in special laws such as the Computer Crimes Law and و. But the emergence of prominent criminal acts, such as economic crimes and organized corruption, led to; the legislator should leave the doubts and distance himself from the different opinions expressed in this regard and approve articles in order to generalize the criminal responsibility of the legal person. Thus, judges and judicial authorities should not be confused in the face of crimes committed by individuals. Legal release. However, the generalization of criminal responsibility in the new Penal Code, although with some shortcomings, has been eliminated to some extent, and this is a positive step. Of course, what works in the current situation is not just the formulation and approval of various laws and volumes. Rather, we must move from quantitative reactions to crimes to qualitative reactions and strengthen the sense of responsibility in the individual members of society. Reduce crime.